Smith e a economia comportamental : prolegômenos de uma teoria da decisão emocional - Pereira, Állirson Oliveira Fortes (2017)
We make decisions at all times, a phenomenon not ignored by the Economics. In recent years, Behavioral Economics (BE) has flourished as a way of incorporating "new" insights into Economic Theory, in particular, to the behavioral postulates of rationality. This dissertation draws a parallel between Adam Smith, the forerunner of Economics and the findings of BE, in order to demonstrate that Adam Smith's Theory of Decision is compatible with elements of modern BE. For this it proposes to rescue the Aristotelian and Scholastic influences of Smith, to form a theory of the decision of Theory of Moral Sentiments and to describe the findings of the BE on the Theory of Decision. The main method used will be the bibliographic revision allied to the analysis of content through the IRaMuTeQ software. Both bibliographic review and content analysis demonstrate that both Smith's Decision Theory and BE's have the following common characteristics: dual decisionmaking, emotional and rational; Simplified models of understanding of reality (heuristics), we clearly identify the heuristic of Affect as similar to the concept of Sympathy; Various cognitive biases, such as loss aversion, oversonfidence, hyperbolic discount, negligence of opportunity cost, effect of identifiable victim; And some very expensive concepts to Smith, such as the natural sense of Justice, Reciprocity, Benevolence, and Illusion of Happiness.